2011
DOI: 10.3390/md9122488
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan, the Marine Functional Food, Is a Potent Adsorbent of Humic Acid

Abstract: Chitosan is prepared by the deacetylation of chitin, the second-most abundant biopolymer in nature, and has applicability in the removal of dyes, heavy metals and radioactive waste for pollution control. In weight-reduction remedies, chitosan is used to form hydrogels with lipids and to depress the intestinal absorption of lipids. In this study, an experimental method was implemented to simulate the effect of chitosan on the adsorption of humic acid in the gastrointestinal tract. The adsorption capacity of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…In addition, the surface of CTS is hydrophilic, and this is conducive for cells to adhere, proliferate and differentiate [16]. Because of these properties chitosan has been recently used to improve currently used CPCs [17][18][19]. However, previous studies have mainly focused on adding chitosan to liquid components of CPCs or preparing chitosan fibers for CPC scaffolds [20,21].…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the surface of CTS is hydrophilic, and this is conducive for cells to adhere, proliferate and differentiate [16]. Because of these properties chitosan has been recently used to improve currently used CPCs [17][18][19]. However, previous studies have mainly focused on adding chitosan to liquid components of CPCs or preparing chitosan fibers for CPC scaffolds [20,21].…”
Section: Introductionmentioning
confidence: 97%
“…8 Chitosan is also recognized as a marine functional food that it is shown to exhibit antidiabetic and antiobesity activity due to the indigestible characteristic acting as dietary fiber. 9,10 Several studies have shown that chitosan can reduce liver cholesterol by decreasing cholesterol absorption and increasing fecal fat excretion in human and animals, which may contribute to weight loss. 11,12 Our previous study has also found that longterm chitosan feeding in a type 2 diabetic rat model suppresses plasma adipocytokines and lipid accumulation in livers and adipose tissues, which may further reduce insulin resistance in diabetic rats.…”
Section: ■ Introductionmentioning
confidence: 99%
“…) and applications in many fields (biotechnology, medicine, membranes, cosmetics, food industry etc. ), but also because of its adsorption potential.…”
Section: Introductionmentioning
confidence: 99%